The Journey: An Approach—From Human Sciences to Theology - Miriam Ramos Gómez; Charlie Jorge Fernández (Religions)
The symbolic value of the journey has been widely explored in literary theory, educational science, history and philosophy. However, is it possible to approach travel from a theological point of view? The aim of our article is to answer this question. In order to do so, we essentially seek a biblical and theological–spiritual foundation for our research. First, we start from the experience contained in travel books as well as from the notion of the journey as a path to wisdom as it appears in some literary works. After examining the pedagogical value of the notion of the journey as an adventure in which the hero is formed, and the philosophical value of the concept of the journey as a search for the meaning of life, we intend to develop the theological approach on three levels: examining the notion of the journey as a metaphor for the Christian way; the experience of the journey as expatriation; and the relationship between the journey and conversion.